Penentuan Formula Biskuit Labu Kuning (Cucurbita moschata) sebagai Pangan Diet Penderita Diabetes Mellitus - Sugitha, IMade; Harsojuwono, Bambang Admadi; Yoga, IWayanGede Sedana (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 2 No 2 (2015), 2015)
The study aims to determine the formula pumpkin biscuits containing resistant starch andbeta-carotene are high but the impact of the increase in blood sugar levels low.The experiment was conducted using a completely randomized design with 5 treatmentscomparison formula pumpkin flour and wheat in the manufacture of biscuits. The comparison isas follows: (40 g : 460 g), (80 g : 420 g), (120 g : 380 g), (160 g : 340 g), and (200 g : 300 g)were repeated 4 times. Research conducted bioassay testing using SD rats. Observations wereresistant starch, beta carotene and increase blood sugar levels. The resulting data were analyzedby ANOVA and Duncan's multiple comparison test.The results showed that the formula biscuits significant effect on levels of resistant starch, betacaroteneand increase blood sugar levels and preference for color, flavor, aroma, texture andoverall acceptance pumpkin biscuits. Formula biscuits with pumpkin comparison and wheat flour(120 g : 380 g) is the best formula. The biscuit formula has the characteristics: resistant starchcontent of 11.79%, beta carotene 9714.21 mg / 100 g and can lower blood sugar increasing up to23.50 mg / dl post-consumption with the preference level of texture ranging from dislike to likeenough, as well as the color, flavor, aroma and overall acceptance between enough like to like.
Keywords: pumpkin flour; wheat flour; biscuit formula; diabetes mellitus